Evaluating the impacts of lease decay on condominiums in Singapore: Bala's table revisited - Aw, Vernice Ming Hui (Nanyang Technological University, 2024)
This paper attempts to analyse the effects of lease decay on freehold and leasehold non-landed private properties, referred to as condominiums in this paper using data covered from the period 1995 Q1 to 2023 Q3, as well as to investigate the relevancy and accuracy of the Bala’s Table in reflecting the lease decay of condominiums in Singapore at present.